Gold-functionalized magnetic nanoparticles restrict growth of Pseudomonas aeruginosa - Niemirowicz K (Dove Medical Press, 2014)
Katarzyna Niemirowicz,1,2 Izabela Swiecicka,3 Agnieszka Z Wilczewska,4 Iwona Misztalewska,4 Beata Kalska-Szostko,4 Kamil Bienias,2 Robert Bucki,1,5,6 Halina Car21Department of Microbiological and Nanobiomedical Engineering, 2Department of Experimental Pharmacology, Medical University of Bialystok, 3Department of Microbiology, 4Institute of Chemistry, University of Bialystok, Bialystok, 5Faculty of Health Sciences, Jan Kochanowski University, Kielce, Poland; 6Institute for Medicine and Engineering, University of Pennsylvania, Philadelphia, PA, USAAbstract: Superparamagnetic iron oxide nanoparticles (SPIONs) and their derivatives (aminosilane and gold-coated) have been widely investigated in numerous medical applications, including their potential to act as antibacterial drug carriers that may penetrate into bacteria cells and biofilm mass. Pseudomonas aeruginosa is a frequent cause of infection in hospitalized patients, and significant numbers of currently isolated clinical strains are resistant to standard antibiotic therapy. Here we describe the impact of three types of SPIONs on the growth of P. aeruginosa during long-term bacterial culture. Their size, structure, and physicochemical properties were determined using transmission electron microscopy, X-ray diffraction analysis, and Fourier transform infrared spectroscopy. We observed significant inhibition of P. aeruginosa growth in bacterial cultures continued over 96 hours in the presence of gold-functionalized nanoparticles (Fe3O4@Au). At the 48-hour time point, growth of P. aeruginosa, as assessed by the number of colonies grown from treated samples, showed the highest inhibition (decreased by 40%). These data provide strong evidence that Fe3O4@Au can dramatically reduce growth of P. aeruginosa and provide a platform for further study of the antibacterial activity of this nanomaterial.Keywords: antibacterial activity, Pseudomonas aeruginosa, superparamagnetic nanoparticles, iron oxides, gold-coated nanoparticles